Fracture resistance of endodontically treated canines restored with different sizes of fiber post and all-ceramic crowns - TÜRKER, ŞEBNEM BEGÜM (KOREAN ACAD PROSTHODONTICS, 2016)
PURPOSE. The aim of this study was to determine the fracture resistance and the mode of fracture of endodontically treated teeth restored with different fiber posts and all-ceramic crowns. MATERIALS AND METHODS. Two glass fiber reinforced post systems in two different sizes and polyethylene fiber ribbon in two different thicknesses (n=10) were used. The specimens, restored with all-ceramic crowns, were subjected to a compressive load (in N) delivered at a 130-degree angle to the long axis until a fracture could be noted. The results were analyzed statistically with a One-Way ANOVA test (P<.05). RESULTS. Statistically significant differences were observed between the mean fracture resistance values of Postec, Snowlight, and Kerr Connect thin specimens (P<.0095). The Postec results (395.70 N) were found to be significantly higher than the others. No statistical difference was observed among the thick specimens (P<.2657). The mean fracture resistance values of the Snowlight thick samples were found to be higher than those of the Snowlight thin samples. The specimens were always fractured around the cemento-enamel junction at the palatinal side. No post fracture was observed for the thin Snowlight and Kerr Connect specimens or for the thick Postec and Kerr Connect specimens. Among the common failure types of the specimens, the worst was observed to be the root fracture failure. The highest post dislodgement failure result (80%) was obtained from the thin Kerr Connect specimen. CONCLUSION. In terms of optimizing fracture resistance, the fiber post size selection should be done according to the forces applied to the restored teeth.
Keywords: Fiber post; Fracture resistance; Post and composite core; IN-VITRO; CORE MATERIALS; PREFABRICATED POSTS; STRESS-DISTRIBUTION; FERRULE LENGTH; BOND STRENGTH; GLASS-FIBER; TEETH; SYSTEMS; RETENTION